MANAJEMEN KELAS DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI KELAS VI SD NEGERI 017 PASIR EMAS KECAMATAN SINGINGI - Mustikomah Mustikomah; Andrizal Andrizal; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2020)
Aspects of management have become scientific, but there are still many elements of management that remain a separate problem for a manager. Many education experts say that learning in the classroom is a treatment to imprison the minds of students, but if in our classes we design it conducive and consider the psychological elements of students, then the class will be a pleasant place. Many advantages can be learned in learning students in class. This research was conducted by the author in order to find out classroom management in increasing students' learning motivation in class VI SD Negeri 017 Pasir Emas Singingi District. To find out the factors that influence classroom management in increasing student learning motivation in class VI SD Negeri 017 Pasir Emas Singingi District. From this study it can be concluded that classroom management has a large impact on student motivation from observations conducted at the beginning of the study conducted random interviews which were asked of students and the teacher was obtained that the importance of classmanagement so that class activities take place well this is also supported with the results of interviewsconducted on 15 students grade VI and a teacher who is the homeroom teacher of class VI. Motivationto learn can grow because there are two supporting indicators, namely intrinsic motivation and extrinsic motivation, which of these two motivations is greatest in intrinsic motivation, where the feeling of pleasure and love that medalam can present a good spirit to foster love for learning.Keywords: Class Management, and Learning Motivation.